PENGARUH BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. NUTRIFOOD INDONESIA DI JAKARTA - Widagdo, Hasbi; Handaru, Agung Wahyu; Pangeran, Andi (Fakultas Ekonomi, Universitas Negeri Jakarta, 2013)
The purpose of this researched is to find out how big is the effect of organization culture toward job satisfaction, organizational commitment toward job satisfaction and organization culture and organizational commitment toward job satisfaction, especially on the employee’s in the marketing, sales and distribution and manufacturing division in PT. Nutrifood Indonesia. The analysis implemented research simple regression and multiple regression analysis. The method of this research is simple random sampling, that took 115 employees in population and the number of sample were 90 responden. The data collected by using questionnaire and cultivated using SPSS 19.0. This research shows these following results: 1) Determination of organizational culture on employee job satisfaction is 45,3%; 2) Determination of organizational commitment on employee job satisfaction is 35,6%; 3) Determination of organizational culture and organizational commitment on employee job satisfaction simultaneously is 44,7%. Keywords: organizational culture, organizational commitment and job satisfaction